2011
DOI: 10.1093/cid/ciq065
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Colonization by Neisseria lactamica and Induction of Protective Immunity against Neisseria meningitidis

Abstract: Carriers of N. lactamica develop mucosal and systemic humoral immunity to N. lactamica together with cross-reacting systemic opsonophagocytic but not bactericidal antibodies to N. meningitidis. Possession of humoral immunity to N. lactamica inhibits acquisition of N. lactamica but not of N. meningitidis. Some individuals are intrinsically resistant to N. lactamica carriage, independent of humoral immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 28 publications
1
62
1
1
Order By: Relevance
“…Most of these are considered commensals of the human nasopharynx, although some have occasionally caused disease in immune-compromised hosts, or systemic infection, which has resulted following animal bites in susceptible individuals. The commensal Neisseria lactamica, in particular, has received significant attention for its potential to protect against N. meningitidis either through natural immunity (from carriage) (Evans et al, 2011) or by informing vaccine design. N. lactamica is a lactose-fermenting human commensal that is closely related to N. meningitidis (Bennett et al, 2005;Hollis et al, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these are considered commensals of the human nasopharynx, although some have occasionally caused disease in immune-compromised hosts, or systemic infection, which has resulted following animal bites in susceptible individuals. The commensal Neisseria lactamica, in particular, has received significant attention for its potential to protect against N. meningitidis either through natural immunity (from carriage) (Evans et al, 2011) or by informing vaccine design. N. lactamica is a lactose-fermenting human commensal that is closely related to N. meningitidis (Bennett et al, 2005;Hollis et al, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…N. lactamica expresses antigens similar to those expressed by N. meningitidis, and sera from mice immunized with N. lactamica enhance N. meningitidis killing, 103 and human carriage of N. lactamica results in a high titer of antibodies to N. meningitidis. 104 Outer membrane proteins and lipooligosaccharide structures common to both species are the major antigenic sources of crossprotection. 105 N. lactamica colonization has been studied as a vaccination strategy to prevent N. meningitidis disease.…”
Section: Cross-reactive Protection Between Commensal and Potentially mentioning
confidence: 99%
“…In one study of colonization of healthy volunteers, the mucosal and systemic antibody response against N. lactamica was cross-reactive against N. meningitidis. However, while these antibodies were opsonophagocytic in vitro, they had poor 104 In fact, there has been some evidence to suggest that N. lactamica even protects N. meningitidis during colonization by triggering antibody-independent responses that do not induce a memory response. 106 Nonetheless, the immunological response to colonization with N. lactamica could potentially protect against systemic infection with N. meningitidis, and further investigation of this strategy is ongoing.…”
Section: Cross-reactive Protection Between Commensal and Potentially mentioning
confidence: 99%
See 1 more Smart Citation
“…However, we found that over 60% of the volunteers carried the N. lactamica strain following challenge, some for many months. 9 Analysis of pre-existing serological responses did not indicate why some individuals developed carriage and some did not and the immune responses following carriage were generally low grade. However, it was interesting that individuals who were given intranasal N. lactamica did not carry N. meningitidis during 6 months of follow-up.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%